THE EFFECTS OF SIMULATION GAMES IN NURSING STUDENTS’ SELF-EVALUATED CLINICAL REASONING SKILLS - Havola, Sara (My University, 2020)
Nursing students can learn clinical reasoning skills by using simulation games. However, there is limited research of this subject. Research is needed especially regarding the use of virtual reality (VR) simulation. Furthermore, game metrics of simulation games should study to have an objective data of how nursing students learn clinical reasoning skills by using simulation games. The purpose of this Master’s Thesis was to evaluate two kinds of simulation games’ effects on self-evaluated clinical reasoning skills by nursing students after playing the computer-based simulation game and the VR simulation. This study consists of systematic literature search and an empirical study. The empirical study was conducted at one university of applied sciences in Finland. Participants were graduating nursing students (n=40). Students played independently the computer-based simulation game at home. The VR simulation gaming sessions were conducted at university of applied sciences. The data were collected by using the Clinical Reasoning Skills scale (CRSs) in three phases: 1) before playing the computer-based simulation, 2) after playing the computer-based simulation and 3) after playing the VR simulation. Data were analysed using relevant statistical methods. Results of this study showed that nursing students’ self-evaluated clinical reasoning skills improved systematically after played the computer-based simulation game and the VR simulation. Results of game metrics showed that playing time was longer when nursing students engaged in the VR simulation than engaged in the computer-based simulation game. Moreover, there was relationship between better playing score and better self-evaluated clinical reasoning skills in playing both kind of simulation games. Further research is needed especially regarding learning clinical reasoning skills by using VR simulation. More research is highly needed regarding game metrics of simulation games and their impacts on nursing students’ clinical reasoning skills. Furthermore, the relationships between game metrics and nursing students clinical reasoning skills should studied more. Empirical part of Master’s Thesis has been reported in a scientific article. The manuscript of an empirical scientific article has submitted to international journal.

Simulaatiopeleillä sairaanhoitajaopiskelijat voivat oppia kliinisen päätöksenteon osaamista. Tutkimusta aiheesta on kuitenkin tehty vähän. Tutkimusta tarvitaan erityisesti virtuaalisimulaation käytöstä. Lisäksi simulaatiopelien pelillisiä parametreja tutkimalla saadaan objektiivista tietoja siitä, kuinka opiskelijat oppivat kliinistä päätöksenteon osaamista simulaatiopeleissä. Tämän pro gradu -tutkielman tarkoituksena oli analysoida kahden eri simulaatiopelin (tietokonepohjainen ja virtuaalisimulaatio) vaikutusta sairaanhoitajaopiskelijoiden kliinisen päätöksenteon osaamiseen. Tutkimus sisältää sekä kirjallisuuskatsauksen että empiirisen tutkimuksen. Empiirinen tutkimus toteutettiin yhdessä suomalaisessa ammattikorkeakoulussa. Tutkimukseen osallistujat olivat valmistuvia sairaanhoitajaopiskelijoita (n=40). Opiskelijat pelasit tietokonepohjaista simulaatiopeliä kotona itsenäisesti. Virtuaalisimulaation pelaaminen järjestettiin ammattikorkeakoulussa. Aineisto kerättiin Kliininen päätöksenteko-osaaminen -mittarilla kolmessa eri vaiheessa: 1) ennen tietokonepohjaista simulaatiopeliä, 2) tietokonepohjaisen simulaatiopelin jälkeen sekä 3) virtuaalisimulaation jälkeen. Aineisto analysointiin sopivin tilastollisin menetelmin. Tutkimustulosten mukaan sairaanhoitajaopiskelijoiden itsearvioitu päätöksenteon osaaminen parantui systemaattisesti heidän pelattuaan sekä tietokonepohjaista simulaatiopeliä että virtuaalisimulaatiota. Tulokset pelillisistä parametreista osoittivat, että sairaanhoitajaopiskelijoiden peliaika virtuaalisimulaatiossa oli pidempi verrattuna tietokonepohjaiseen simulaatiopeliin. Lisäksi tulokset osoittivat, että paremmilla pelipisteillä ja sairaanhoitajaopiskelijoiden itsearvioidulla kliinisen päätöksenteon osaamisella oli yhteys. Tutkimusta tarvitaan lisää siitä, miten sairaanhoitajaopiskelijat oppivat kliinistä päätöksenteon osaamista virtuaalisimulaation avulla. Lisäksi simulaatiopelien pelillisiä parametrejä ja niiden yhteyttä sairaanhoitajaopiskelijoiden kliinisen päätöksenteon osaamiseen tulee tutkia lisää. Osa pro gradu -tutkielmasta on raportoitu kirjallisuuskatsauksesta erillisenä tieteellisenä artikkelina. Empiirisestä tutkimuksesta kirjoitettu artikkeli on lähetetty arvioitavaksi kansainväliseen tieteelliseen julkaisuun.
Keywords: simulation game, game metrics, clinical reasoning skills, nursing students simulaatiopeli, pelilliset parametrit, kliininen päätöksenteon osaaminen, sairaanhoitajaopiskelijat